Hadith Criticism of Rain-Shaman Practices in Muslim Community Wedding Traditions - Anggun Fadila; Husnel Anwar Matondang (International Journal of Multidisciplinary Research of Higher Education, 2026)
Rain-shaman practices remain embedded in certain Muslim community wedding traditions in Indonesia. These practices warrant scholarly examination as they reflect the intersection of local cultural traditions, communal religious understanding, and the principle of tawhid in Islamic teachings. This study aims to analyze the forms of rain-shaman practices within wedding ceremonies and to evaluate their conformity with Islamic hadith through the methodological framework of sanad and matan criticism. Employing a qualitative field research design, data were collected through observation, in-depth interviews, and documentation involving rain-shamans, religious leaders, cultural figures, and community members. Data analysis followed the Miles and Huberman model, encompassing data reduction, presentation, and conclusion drawing, reinforced by hadith criticism. Findings reveal diverse practices: some involve supplications directed to Allah, which may be interpreted as religious efforts (ikhtiar), while others employ symbolic media such as chili, salt, nails, and offerings, accompanied by beliefs in the shaman’s special powers elements lacking strong hadith foundations and potentially conflicting with the principle of tawhid. The study concludes that hadith criticism provides a normative framework for proportionally evaluating local religious practices, balancing cultural heritage with Islamic orthodoxy.